PATHOLOGICAL AND MOLECULAR PARAMETERS SHOW NO SIGNIFICANT ASSOCIATION WITH RESIDUAL CANCER BURDEN IN BREAST CARCINOMA - Rahmanti, Fishella Aprista; Sandhika, Willy; Tjandra, Lusiani (Folia Medica Indonesiana, 2025)
Residual Cancer Burden (RCB) is a validated scoring system that quantifies the amount of tumour remaining after neoadjuvant chemotherapy (NAC) for breast cancer, providing prognostic information beyond binary outcomes, such as pathologic complete response (pCR). pCR represents a binary endpoint within various NAC response-grading systems, including RCB, rather than a separate reporting system. This study aimed to assess clinicopathological and molecular predictors of RCB class, including histological grade, histopathological type, molecular subtype, and Ki-67 index. A retrospective study was conducted on 68 patients diagnosed with breast carcinoma who underwent NAC. Descriptive statistics and Pearson, Spearman, and chi-square tests were used to evaluate associations between these variables and RCB class. The mean Ki-67 index was 49.9% (standard deviation not specified), and most tumours were grade 2 (48.5%), invasive carcinoma of no special type (79.4%), and luminal B subtype (63.2%). The distribution of RCB classes was RCB III (42.6%), RCB II (35.3%), RCB 0 (13.2%), and RCB I (8.8%). Statistical analysis did not reveal significant associations between histological grade, histopathological type, molecular subtype, or Ki-67 and RCB class (all p > 0.05). No statistically significant associations were identified; however, the study may be insufficiently powered to detect smaller but clinically meaningful relationships. These findings point to the need for larger, multicentre studies with standardised biomarker assessment to improve post-treatment prognostication.